Contribution of Hormonal Cytology in Girls and Adolescents to Reproductive Health: A Traditional Technique Monitoring Recent Problems - Dušková, Jaroslava; Goldová, Barbara; Matiášková, Lenka; Beková, Alena; Skřenková, Jana (Acta cytologica, 2017)
OBJECTIVE: To study the contribution of hormonal cytology in contemporary disturbances of fertility. DESIGN: Over a 10-year period (2006-2015), 6,688 vaginal fornix cytologies of 2,350 patients were investigated. For a more detailed analysis, a 3-year period from 2013 to 2015 was chosen. Four hundred and fifty-two patients were investigated, many of them several times and for a period longer than the 3 years analyzed. RESULTS: The main disorders examined and treated via a gentle hormonal medication support and life style corrections by a pediatric gynecologist were: pubertas praecox - thelarche praecox and early menarche; dysfunctional juvenile metrorrhagia; central and peripheral endocrine disorders; eating disorders - anorexia mentalis and bulimia; obesity; excessive sport activities; autoimmune disorders, and others. Normalization of the menstrual cycle was achieved while monitoring progress with a series of hormonal cytologies in a majority of patients. CONCLUSIONS: Hormonal cytology is a non-invasive and economical method, illustrating the direct effect of steroid on target cells. It contributes to reproductive health support by: (a) indicating the possible need and type of steroid therapy; (b) monitoring the normalization of cycle disturbances; (c) ruling out or indicating the need for more detailed steroid metabolism investigation. Thus, it represents a basic but valuable means of examination in child and adolescent gynecology.
Keywords: Disorders of menstrual cycle; Infant; Humans; Endocrine cytology; Reproductive Health; kojenec; lidé středního věku; Pediatric gynecology; dítě; Predictive Value of Tests; Child; cytodiagnostika; vaginální stěr; Female; mladý dospělý; dospělí; Progestins; fertilita; věkové faktory; výsledek terapie; ženská infertilita; Infertility, Female; lidé; reprodukční zdraví; Cytodiagnosis; reprodukovatelnost výsledků; časové faktory; Vagina; menstruační cyklus; progestiny; vagina; předškolní dítě; Adult; ženské pohlaví; Menstrual Cycle; Papanicolaou Test; Papanicolaouův test; Middle Aged; prediktivní hodnota testů; Fertility; Reproducibility of Results; Disorders of food intake; Adolescent; Treatment Outcome; Reproductive health; estrogeny; Estrogens; Pubertas praecox; Young Adult; Vaginal Smears; Age Factors; Hormonal cytology; Child, Preschool; Time Factors; mladiství